STRUCTURAL BEHAVIOR OF PILE CAP 3 PILE WITH EKSENTRIC LOAD DESIGNED USING STRUT AND TIE MODEL WITH NUMERICAL METHOD - Panji Ginaya Taufik; Djoko Sulistyo; Akhmad Aminullah (Media Teknik Sipil, 2019)
Pile cap is a structure to distribute load from the upper structure to the sub structure. Often the planning of the pile cap is approached as a two way slab or beam with pile as restrain, by consider the bending and shear separately. As is the case with conventional methods that consider 1-way shear, 2-way shear, and bending separately. The strut and tie model can be used as an alternative method in designing a pile cap, by approaching the stress trajectory with the truss model. In this study, a pile cap will be designed using the conventional method and the strut and tie model, the pile cap with 3 pile cap and an eccentric load. Then the results are tested numerically using Abaqus to determine the difference in behavior. The main reinforcement results from the strut and tie model method are more evenly stressed than the conventional method, also the vertical load needed to achieve the main reinforcement yield stress strut and tie model (1100 kN) is greater than the conventional method (900 kN).